Potassium-sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability and preparation method of potassium-sodium niobate-based textured piezoelectric ceramic

Through the solid phase synthesis method and template grain growth method combined with casting process and two-step sintering process, a potassium sodium niobate-based piezoelectric ceramic with polycrystalline phase boundary and large-scale domain structure was constructed, which solved its shortcomings in high-voltage electrical response and temperature stability, and achieved efficient sensing output over a wide temperature range.

CN119797914AActive Publication Date: 2025-04-11TONGJI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411856548.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-11
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Potassium sodium niobate-based piezoelectric ceramics have shortcomings in high-voltage electrical response and temperature stability, making it difficult to maintain a reliable and stable sensing output over a wide operating temperature range.

Method used

Through solid-phase synthesis method, template grain growth method combined with casting process and two-step sintering process, room temperature polycrystalline phase boundary and large-scale domain structure are constructed, and the chemical composition and crystal orientation of the ceramic are optimized to improve piezoelectric performance and temperature stability.

Benefits of technology

It realizes high-voltage electrical response and excellent temperature stability. The piezoelectric coefficient and inverse piezoelectric coefficient change rate are small in the temperature range of 25-200℃, and are suitable for applications in medium and high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797914A_ABST
    Figure CN119797914A_ABST
Patent Text Reader

Abstract

The invention relates to a potassium-sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability and a preparation method thereof, the chemical general formula of the textured piezoelectric ceramic is (0.98-x) ((K < 0.49 > Na < 0.49 > Li < 0.02 >) (Nb < 0.96 > Sb < 0.04 >) O < 3 >)-0.02 ((Bi < 0.5 > Na < 0.5 >) (Zr < 0.8 > Ti < 0.2 >) O < 3 >)-x (CaZrO < 3 >) + 4wt.% NaNbO < 3 >, x is more than or equal to 0.01 and less than or equal to 0.04; the method comprises a solid-phase synthesis method, a two-step molten salt method combined separation method, a template grain growth method, a tape casting process, a hot pressing process, a glue discharging process, a two-step sintering process, a silver firing process and a polarization process. Compared with the prior art, the KNN-based lead-free texture piezoelectric ceramic with high piezoelectric response can be obtained by combining a solid-phase synthesis method and a template grain growth method with a tape casting process and a two-step sintering process. More importantly, the change rate of the piezoelectric coefficient and the inverse piezoelectric coefficient in a wide temperature range can be small by constructing a polycrystalline phase boundary and a regulation domain structure, and the temperature stability is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional ceramics, and relates to a potassium sodium niobate-based textured piezoelectric ceramic with high-voltage electrical response and temperature stability and a preparation method thereof. Background Art

[0002] Piezoelectric ceramics are an information functional ceramic material that can realize the mutual conversion of mechanical energy and electrical energy. They are the core material for manufacturing electronic components with mechanical-electrical conversion functions and have been widely used in medical imaging, acoustic sensors, acoustic transducers, ultrasonic motors, etc.

[0003] At present, lead titanate and lead zirconate titanate based piezoelectric ceramics have been occupying the main share of the piezoelectric material market due to their high piezoelectric response and excellent temperature stability. However, their raw materials have high lead content and high toxicity, which will cause great harm to personnel and environmental pollution during production and recycling, and pose great safety hazards. Therefore, the research and development of high-performance and high-stability lead-free piezoelectric materials comparable to traditional PZT-based piezoelectric ceramic materials for application in electronic components has important strategic significance and economic value.

[0004] Potassium sodium niobate ((K,Na)NbO3, KNN) ceramics are considered to be one of the most promising candidates for lead-free piezoelectric ceramics due to their relatively good comprehensive properties. Although pure potassium sodium niobate lead-free piezoelectric ceramics have a high Curie temperature (~430°C), their ferroelectric and piezoelectric properties are relatively poor. The piezoelectric coefficient d of the unmodified (K,Na)NbO3 ceramics obtained by the traditional solid phase sintering method is 33 Generally, it is 80-120pC / N, which is still far from the piezoelectric performance of lead-based ceramics. At present, the research on lead-free piezoelectric ceramics based on potassium sodium niobate mainly focuses on improving electrical properties and temperature stability. The piezoelectric performance of ceramics is improved mainly by regulating the chemical composition to construct polymorphic phase boundaries at room temperature and preparing textured ceramics to control crystal orientation, and good progress has been made.

[0005] Patent CN116639974A discloses a piezoelectric ceramic material with high voltage electrical response and its preparation method, the stoichiometric ratio conforms to the chemical formula 0.95 (K 0.55 Na 0.45 )NbO3-0.05LiTaO3-x mol.%Sm2O3; wherein, 0.2≤x≤0.6. This patent obtains good piezoelectric properties through rare earth doping modification, but has not been optimized in terms of Curie temperature and temperature stability, which limits its application in medium and high temperature environments.

[0006] Patent CN117125981A discloses a temperature-stable potassium sodium niobate multilayer composite textured ceramic. By constructing multilayer composite ceramics with different components, the piezoelectric coefficient d33 and d 33 * The change rates are less than 5% and 2% respectively. The ceramic material has high application value in the fields of high-temperature piezoelectric sensors and energy harvesters.

[0007] Existing patents on small signal piezoelectric coefficient d 33 There have been great breakthroughs in the improvement of piezoelectricity, that is, obtaining a very high piezoelectric response; but from the perspective of piezoelectric material application, the quality factor of the material is the small signal piezoelectric coefficient d 33 and operating temperature range, while potassium sodium niobate-based piezoelectric ceramics have always been difficult to break through the piezoelectric coefficient d 33 The problem of poor temperature stability: while obtaining high-voltage electrical response, no attention is paid to its temperature stability. Generally, the higher the piezoelectric performance, the lower the Curie temperature, and reliable and stable sensor output cannot be guaranteed within a wide operating temperature range. Summary of the invention

[0008] The purpose of the present invention is to overcome at least one defect of the above-mentioned prior art and to provide a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability and a preparation method thereof. The present invention can obtain lead-free textured piezoelectric ceramics with high piezoelectric response through solid phase synthesis, template grain growth method combined with casting process and two-step sintering process. More importantly, by constructing room temperature polycrystalline phase boundaries and large-scale domain structures, the piezoelectric coefficient and the inverse piezoelectric coefficient have a small change rate in a wide temperature range and have excellent temperature stability.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] One of the technical solutions of the present invention is to provide a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, the chemical formula of the textured piezoelectric ceramic is (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3)-(CaZrO3)x+4wt.% (relative to the mass of the entire powder)NaNbO3, 0≤x≤0.04.

[0011] As a preferred technical solution, the x is 0, 0.01, 0.02, 0.03 or 0.04.

[0012] As a preferred technical solution, the x is 0.03 or 0.04.

[0013] As a preferred technical solution, the x is 0.03.

[0014] As a preferred technical solution, the textured piezoelectric ceramic grains are oriented in <001> C >95.0%.

[0015] Furthermore, when x is 0.03, <001> C The grain size is about 20-50 μm, and the dielectric constant remains stable from room temperature to Curie temperature. It has good piezoelectric properties. Its piezoelectric coefficient d 33 It is 520pC / N, and the inverse piezoelectric coefficient is 525pm / V under an electric field of 40kV / cm. The piezoelectric coefficient first remains stable and then increases slightly with increasing temperature. The piezoelectric coefficient changes by 3.8% in the temperature range of 25-200°C, showing excellent temperature stability. The unipolar strain first remains stable and then increases slightly with increasing temperature. Correspondingly, it can be calculated that the inverse piezoelectric coefficient changes by 4.2% in the temperature range of 25-200°C, showing excellent temperature stability.

[0016] One of the technical solutions of the present invention is to provide a method for preparing a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, the method comprising the following steps:

[0017] (1) Solid phase synthesis method: Sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium oxide (Nb2O5), bismuth oxide (Bi2O3), zirconium oxide (ZrO2), lithium carbonate (Li2CO3), calcium carbonate (CaCO3), antimony oxide (Sb2O3), and titanium oxide (TiO2) are selected, weighed according to the chemical composition, added with ball milling media, ball milled and mixed thoroughly, discharged and dried to obtain a powder base material;

[0018] (2) Two-step molten salt method combined with separation method: In the first step, bismuth oxide, potassium carbonate, niobium oxide and molten salt are synthesized, separated and filtered to obtain a flake precursor (Bi 2.5 Na 3.5 Nb5O 18 ), and in the second step, the flake precursor is synthesized with potassium carbonate and molten salt, separated and filtered to obtain a high-quality pure sodium niobate (NaNbO3) flake template;

[0019] (3) Template grain growth method: The powder base material obtained in step (1) and the sheet template obtained in step (2) are added with a mixed solvent, a dispersant, a plasticizer and a binder respectively, and mixed by a roller mill to obtain a casting slurry;

[0020] (4) Casting process: The casting slurry obtained in step (3) is cast using a convenient and small coating machine, and then dried to form a dry thick film with certain toughness and plasticity;

[0021] (5) hot pressing process: the dried thick film obtained in step (4) is cut into a desired shape and stacked layer by layer for 16 to 18 layers, and finally hot pressed to form a ceramic green body;

[0022] (6) debinding process: placing the ceramic green body obtained in step (5) in a muffle furnace for debinding to obtain a ceramic green body;

[0023] (7) Two-step sintering process: The ceramic body obtained in step (6) is subjected to two-step sintering, and after naturally cooling to room temperature, it is ground and polished with sandpaper to obtain a ceramic sheet;

[0024] (8) Silver firing process: The ceramic sheet obtained in step (7) is coated with silver paste and placed in a muffle furnace for silver firing to obtain a ceramic coated with a silver electrode, which is then subjected to electrical testing;

[0025] (9) Polarization process: The ceramic coated with silver electrodes obtained in step (8) is placed in a silicone oil bath for polarization to obtain a potassium sodium niobate-based textured piezoelectric ceramic with temperature stability.

[0026] As a preferred technical solution, the first half of the chemical formula (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3)-(CaZrO3)x+4wt.%NaNbO3 was prepared by solid phase synthesis, and the latter part (4wt.%NaNbO3) was prepared by a two-step molten salt method combined with a flake template prepared by a separation method.

[0027] Furthermore, in step (1), the ball milling medium is ethanol, and the milling time is 12-24 hours.

[0028] Furthermore, in step (2), the molten salt is sodium chloride (NaCl), the total mass ratio of the raw materials in the first step and the second step (the raw materials refer to the base materials other than sodium chloride in the preparation process of the first step and the second step, that is, the raw materials in the first step refer to bismuth oxide, potassium carbonate, and niobium oxide, and the raw materials in the second step refer to the flake precursor and potassium carbonate) and the molten salt in the corresponding step is 1:1.1 (that is, the total mass ratio of bismuth oxide, potassium carbonate, and niobium oxide in the first step to the molten salt in the first step is 1:1.1, the total mass ratio of the flake precursor and potassium carbonate in the second step to the molten salt in the second step is 1:1.1), the insulation time is 2h, the molar ratio of bismuth oxide, potassium carbonate and niobium oxide in the first step is 6.5:7:10, and the melting temperature is 1050-1100°C, and the molar ratio of the flake precursor and potassium carbonate in the second step is 1:1.75, and the melting temperature is 970-1000°C;

[0029] In step (2), sodium tripolyphosphate is used as the separation reagent, and the amount of separation reagent added is 8-10wt.% of the total mass of the molten salt mixture of the first or second step, the stirring speed is 600-800rpm, and the time is 5-10min. That is, the amount of separation reagent added in the first step is 8-10wt.% of the total mass of bismuth oxide, potassium carbonate, niobium oxide and molten salt mixture in the first step, and the amount of separation reagent added in the second step is 8-10wt.% of the total mass of the flake precursor, potassium carbonate and molten salt mixture in the second step.

[0030] As a preferred technical solution, the aspect ratio of the sheet template in step (2) is (10-15):1.

[0031] Furthermore, in step (3), the mixed solvent is butanone and ethanol, the dispersant is triolein, the plasticizer is polyethylene glycol and dibutyl phthalate, the binder is polyvinyl butyral (PVB), the mass ratio of the powder base material, the sheet template and the reagents (butanone, ethanol, triolein, polyethylene glycol, dibutyl phthalate and polyvinyl butyral) is (8.4-9):(0.3-0.4):(8-10):(4-6):(0.3-0.35):(0.4-0.5):(0.35-0.5):(1.1-1.2), the mixing speed is 16-18 r / min, and the time is 6-8 h.

[0032] Furthermore, in step (4), a casting scraper is used for casting, and the moving speed of the casting scraper is 28-30 cm / min.

[0033] As a preferred technical solution, the thickness of the dried thick film in step (4) is 10-15 μm.

[0034] As a preferred technical solution, in step (5), the hot pressing temperature is 45-55°C, the pressure is 8-12 MPa, and the time is 0.3-0.5 h. Wherein, stacking layer by layer means: stacking 16 to 18 layers.

[0035] Furthermore, in step (6), the debinding temperature is 550-600° C. and the insulation time is 10-12 h.

[0036] Furthermore, the two-step sintering in step (7) includes a first step and a second step, wherein the first step has a heating rate of 2-5°C / min, a heating temperature of 1160-1200°C, and no heat preservation, and the second step has a cooling rate of 10-15°C / min, a cooling temperature of 1060-1100°C, and a heat preservation time of 8-12h.

[0037] As a preferred technical solution, in step (7), the sandpaper particle size is 400-2000 mesh, and the grinding thickness is 0.3-0.6 mm.

[0038] Furthermore, in step (8), the diameter of the silver paste is 4-6 mm, the silver sintering temperature is 550-600° C., and the insulation time is 20-30 min.

[0039] Furthermore, in step (9), the polarization electric field is 2-4 kV / mm and the time is 20-30 min.

[0040] In order to obtain KNN-based piezoelectric ceramic materials with high piezoelectric response and excellent temperature stability, multiphase coexistence in a wide temperature range was constructed by chemical doping. CaZrO3 with a tunable phase boundary temperature was doped into (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3) matrix, successfully lowered the ferroelectric phase transition temperature T O-T Adjust to room temperature. The reason for choosing this basic system is that, on the one hand, the doping of multiple ions plays a synergistic optimization role for the potassium sodium niobate matrix, making the system have a higher piezoelectric response. On the other hand, systems similar to this basic system all have piezoelectric properties above 400pC / N, which provides a basis for this work to have a higher piezoelectric response. At the same time, the template grain growth technology (TGG) was used to obtain <001> COriented piezoelectric ceramics make the improvement of piezoelectric performance more dependent on the contribution of piezoelectric anisotropy, thereby reducing the impact of reduced temperature stability caused by temperature-induced phase change. Therefore, the present invention can improve piezoelectric performance while improving temperature stability. The present invention provides a good design idea for the development of practical advanced functional materials and is a major breakthrough in realizing the future application of KNN-based piezoelectric ceramics in medium and high temperature environments.

[0041] Compared with the existing related inventions, the present invention has the following advantages:

[0042] (1) The present invention can obtain lead-free textured piezoelectric ceramics with high piezoelectric performance (520pC / N) through solid phase synthesis, template grain growth method combined with tape casting process and two-step sintering process; more importantly, its piezoelectric coefficient changes by 3.8% in the temperature range of 25-200°C; the large signal inverse piezoelectric coefficient changes by 4.2% in the temperature range of 25-200°C. It is of great significance for the development of high temperature and high voltage lead-free piezoelectric materials, and has high application value in the fields of low and medium temperature transducers, sensors, drivers and electric actuators;

[0043] (2) The preparation method of the present invention is simple, economical and practical, and is a lead-free material. It will not pollute the environment during the preparation, application and disposal process, and is an environmentally friendly high-performance piezoelectric material. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 X-ray diffraction (XRD) diagrams of the piezoelectric ceramics in Comparative Example 1 and Examples 2 to 5 of the present invention;

[0045] Figure 2 This is a scanning electron microscope (SEM) image of the potassium sodium niobate-based textured piezoelectric ceramic with high Curie temperature and temperature stability in Example 4 of the present invention;

[0046] Figure 3 The dielectric temperature spectra of the piezoelectric ceramics in Comparative Example 1 and Examples 2 to 5 of the present invention;

[0047] Figure 4 hysteresis loop diagrams of the piezoelectric ceramics in Comparative Example 1 and Examples 2 to 5 of the present invention;

[0048] Figure 5 The in-situ temperature-dependent piezoelectric coefficient diagram of the piezoelectric ceramics in Comparative Example 1 and Examples 2 to 5 of the present invention;

[0049] Figure 6 The unipolar strain diagrams of the potassium sodium niobate-based textured piezoelectric ceramics with high-voltage electrical response and temperature stability at different temperatures in Example 4 of the present invention are shown;

[0050] Figure 7The in-situ temperature-dependent inverse piezoelectric coefficient diagram of the piezoelectric ceramics in Comparative Example 1 and Examples 2 to 5 of the present invention;

[0051] Figure 8 Statistical graphs of the piezoelectric coefficient and Curie temperature of the piezoelectric ceramics in Comparative Example 1 and Examples 2 to 5 of the present invention. DETAILED DESCRIPTION

[0052] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the accompanying drawings and the following embodiments are only used to illustrate the present invention, rather than to limit the present invention. It should be pointed out that for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0053] The present invention relates to a potassium sodium niobate-based textured piezoelectric ceramic with high voltage electrical response and temperature stability and a preparation method thereof. The textured piezoelectric ceramic has a chemical formula of (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3)-x(CaZrO3)+4wt.%NaNbO3, 0.01≤x≤0.04; the method includes solid phase synthesis method, two-step molten salt method combined with separation method, template grain growth method, tape casting process, hot pressing process, debinding process, two-step sintering process, silver burning process and polarization process. Compared with the prior art, the present invention can obtain KNN-based lead-free textured piezoelectric ceramics with high piezoelectric response through solid phase synthesis method, template grain growth method combined with tape casting process and two-step sintering process. More importantly, by constructing polycrystalline phase boundaries and regulating domain structures, the piezoelectric coefficient and the inverse piezoelectric coefficient can have a small change rate in a wide temperature range, and have excellent temperature stability.

[0054] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.

[0055] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0056] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.

[0057] Sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium oxide (Nb2O5), bismuth oxide (Bi2O3), zirconium oxide (ZrO2), lithium carbonate (Li2CO3), calcium carbonate (CaCO3), antimony oxide (Sb2O3), titanium oxide (TiO2) have a purity greater than 99%, and all drugs are from Aladdin Chemical Reagent Co., Ltd. and Sinopharm Reagent Co., Ltd. Butanone, ethanol, triolein, polyethylene glycol, dibutyl phthalate and polyvinyl butyral, except for polyvinyl butyral from Aladdin Chemical Reagent Co., Ltd., with a molecular weight of 90,000-120,000, all others are from Sinopharm Chemical Reagent Co., Ltd., and are all chemically pure.

[0058] Comparative Example 1:

[0059] This comparative example provides a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, the chemical composition of which is 0.98 ((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3)+4wt.%NaNbO3, the specific steps of the preparation method are as follows:

[0060] (1) 4.4764 g Na2CO3, 5.7180 g K2CO3, 21.5458 g Nb2O5, 0.4015 g Bi2O3, 0.3397 g ZrO2, 0.1248 g Li2CO3, 0.9846 g Sb2O3, and 0.0551 g TiO2 were selected as raw materials for textured piezoelectric ceramic materials, the materials were weighed according to the chemical composition, ethanol was added and ball-milled for 24 h, the materials were discharged, and dried to obtain a powder base material;

[0061] (2) The conventional two-step molten salt method combined with the separation method was used. In the first step, 10 g Bi2O3, 3.1942 g K2CO3, 8.7762 g Nb2O5 and 24.1674 g NaCl were used for synthesis, melted and kept at 1100 °C for 3 h, 10 wt% sodium tripolyphosphate (4.6138 g) was added at 600 rpm for separation for 8 min, and filtered to obtain the flake precursor Bi 2.5 Na 3.5 Nb5O 18 In the second step, 8 g of the flake precursor, 1.3705 g of K2CO3 and 10.3076 g of NaCl were used for synthesis, melted and kept at 970°C for 2 h, 10 wt% sodium tripolyphosphate (1.9678 g) was added at 600 rpm, separated for 8 min, and filtered to obtain high-quality pure sodium niobate (NaNbO3) flake template with an aspect ratio of 15:1;

[0062] (3) adding 10 g of butanone and 5 g of ethanol as a mixed solvent, 0.35 g of triolein as a dispersant, 0.4 g of polyethylene glycol and 0.35 g of dibutyl phthalate as a plasticizer, and 1.2 g of polyvinyl butyral (PVB) as a binder to 9.6 g of the powder base material obtained in step (1) and 0.4 g of the sheet template obtained in step (2), and mixing the mixed material on a roller mill at 16 r / min for 7 h to obtain a casting slurry;

[0063] (4) The casting slurry obtained in step (3) is cast using a convenient small coating machine, with the scraper moving speed being 30 cm / min, and then dried to form a dry thick film with certain toughness and plasticity, with a thickness of 12.5 μm;

[0064] (5) cutting the dried thick film obtained in step (4) into a desired shape and stacking the layers, and finally hot pressing at 55° C. and 10 MPa for 0.3 h to form a ceramic green body;

[0065] (6) placing the ceramic green body obtained in step (5) in a muffle furnace for debinding, and keeping the temperature at 600° C. for 10 h to obtain a ceramic green body;

[0066] (7) sintering the ceramic body obtained in step (6) in two steps, heating the temperature to 1160° C. at 3° C. / min without heat preservation, then cooling the temperature to 1060° C. at 10° C. / min, and heat preservation for 10 h. After naturally cooling to room temperature, grinding and polishing with 800-mesh sandpaper to a thickness of 0.6 mm to obtain a ceramic sheet;

[0067] (8) Silver firing process: The ceramic sheet obtained in step (7) is coated with a silver paste having a diameter of 4 mm, placed in a muffle furnace for silver firing, and kept at 550° C. for 30 min to obtain a ceramic coated with a silver electrode, which is then subjected to electrical testing;

[0068] (9) Polarization process: The ceramic coated with silver electrodes obtained in step (8) is placed in a silicone oil bath and polarized for 30 min under an electric field of 4 kV / mm to obtain a potassium sodium niobate-based lead-free textured piezoelectric ceramic with high voltage electrical performance and excellent temperature stability.

[0069] Embodiment 2:

[0070] This embodiment provides a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, the chemical composition of which is (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3)-(CaZrO3)x+4wt.%NaNbO3, 0≤x≤0.04, wherein x=0.01. The preparation method is basically the same as that of Comparative Example 1, except that in step (1), 4.4299g Na2CO3, 5.6575g K2CO3, 21.3178g Nb2O5, 0.4013g Bi2O3, 0.5519g ZrO2, 0.1235g Li2CO3, 0.1724g CaCO3, 0.9742g Sb2O3 and 0.0550g TiO2 are selected as raw materials for textured piezoelectric ceramic materials.

[0071] Embodiment 3:

[0072] This embodiment provides a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, the chemical composition of which is (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2)O3)-(CaZrO3)x+4wt.%NaNbO3, 0≤x≤0.04, wherein x=0.02, the preparation method is basically the same as that of Comparative Example 1, except that in step (1), 4.3835g Na2CO3, 5.5970g K2CO3, 21.0899g Nb2O5, 0.4012g Bi2O3, 0.7638g ZrO2, 0.1221g Li2CO3, 0.3447g CaCO3, 0.9637g Sb2O3, and 0.0550g TiO2 are selected as raw materials for textured piezoelectric ceramic materials. The difference in step (7) is that the temperature is raised to 1180℃ at 3℃ / min without heat preservation, and then dropped to 1080℃ at 10℃ / min and kept warm for 10h.

[0073] Embodiment 4:

[0074] This embodiment provides a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, the chemical composition of which is (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3)-(CaZrO3)x+4wt.%NaNbO3, 0≤x≤0.04, wherein x=0.03, the preparation method is basically the same as that of comparative example 1, except that in step (1), 4.3372g Na2CO3, 5.5366g K2CO3, 20.8623g Nb2O5, 0.4010g Bi2O3, 0.9756g ZrO2, 0.1208g Li2CO3, 0.5168g CaCO3, 0.9533g Sb2O3, and 0.0550g TiO2 are selected as raw materials for textured piezoelectric ceramic materials. The difference in step (7) is that the temperature is raised to 1180℃ at 3℃ / min without heat preservation, and then dropped to 1080℃ at 10℃ / min and kept warm for 10h.

[0075] Example 5

[0076] This embodiment provides a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, the chemical composition of which is (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na0.5 )(Zr 0.8 Ti 0.2 )O3)-(CaZrO3)x+4wt.%NaNbO3, 0≤x≤0.04, wherein x=0.04, the preparation method is basically the same as that of comparative example 1, except that in step (1), 4.2908g Na2CO3, 5.4762g K2CO3, 20.6348g Nb2O5, 0.4009g Bi2O3, 1.1872g ZrO2, 0.1195g Li2CO3, 0.6888g CaCO3, 0.9429g Sb2O3, and 0.0550g TiO2 are selected as raw materials for textured piezoelectric ceramic materials. The difference in step (7) is that the temperature is raised to 1200℃ at 3℃ / min without heat preservation, and then dropped to 1100℃ at 10℃ / min and kept warm for 10h. Each component has a corresponding optimal sintering temperature, and the atlas data are tested based on the optimal sintered samples of each component.

[0077] like Figure 1 As shown in FIG. 1 , the texture degree of the potassium sodium niobate-based textured piezoelectric ceramics with high voltage electrical response and temperature stability of Examples 2 to 5 is calculated using the Lotgering factor f. The texture degree of the potassium sodium niobate-based textured piezoelectric ceramics with high voltage electrical response and temperature stability of Comparative Example 1 is <001> C The texture degree in the direction is relatively high (f=92.8%). The potassium sodium niobate-based textured piezoelectric ceramics with high piezoelectric response and temperature stability in Example 2 are <001> C The texture degree in the direction is very high (f = 95.7%). The potassium sodium niobate-based textured piezoelectric ceramics with high piezoelectric response and temperature stability in Example 3 are <001> C The texture degree in the direction is very high (f = 94.2%). The potassium sodium niobate-based textured piezoelectric ceramics with high piezoelectric response and temperature stability of Example 4 are <001> C The texture degree in the direction is relatively high (f=98.2%). The potassium sodium niobate-based textured piezoelectric ceramics with high piezoelectric response and temperature stability in Example 5 are <001> C The direction has a high texture degree (f = 94.1%). And according to the ratio of the (002) and (200) peak heights, the phase structure of the ceramic can be determined. Figure 1 It can be concluded that in Comparative Example 1 and Examples 2, 3, 4, and 5, orthorhombic tetragonal phases coexist.

[0078] like Figure 2 As shown, by observing the free surface of the ceramic in Example 4, it can be seen that after adding the flake template, the grains grow in an oriented manner and the grain size is about 20-50 μm.

[0079] like Figure 3 ,4 As shown, the dielectric constant of the potassium sodium niobate-based textured piezoelectric ceramics of Example 4 remains stable from room temperature to Curie temperature, which is the reason for its excellent temperature stability. In addition, Example 4 presents a very saturated hysteresis loop, and the residual polarization and saturation polarization are large, so it has excellent ferro / piezoelectric properties, and its piezoelectric coefficient d 33 It is 520pC / N.

[0080] like Figure 5 As shown, the piezoelectric coefficient of Example 4 first remains stable and then decreases as the temperature increases, and the change rate of the piezoelectric coefficient in the temperature range of 25-200° C. is 3.8%, showing excellent temperature stability.

[0081] In view of the stability of the above piezoelectric coefficient, the curve of the inverse piezoelectric coefficient of Example 4 changing with temperature is supplemented, such as Figure 6 As shown in Figure 7, the unipolar strain of Example 4 first remains stable and then decreases with the increase of temperature. Correspondingly, the inverse piezoelectric coefficient can be calculated to be 525pm / V at room temperature, and the change rate is also 4.2% in the temperature range of 25-200℃, showing excellent temperature stability.

[0082] like Figure 8 Shown is a statistical graph of the piezoelectric coefficient and Curie temperature of the piezoelectric ceramics in Comparative Example 1 and Examples 2 to 5 of the present invention.

[0083] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability, characterized in that: The chemical formula of the textured piezoelectric ceramic is (0.98-x)((K 0.49 Na 0.49 Li 0.02 )(Nb 0.96 Sb 0.04 )O3)-0.02((Bi 0.5 Na 0.5 )(Zr 0.8 Ti 0.2 )O3)-x(CaZrO3)+4wt.%NaNbO3, 0.01≤x≤0.

04.

2. A method for preparing a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability as claimed in claim 1, characterized in that: The method comprises the following steps: (1) Solid phase synthesis method: Sodium carbonate, potassium carbonate, niobium oxide, lithium carbonate, calcium carbonate, zirconium oxide, antimony oxide, titanium oxide, and bismuth oxide are selected, weighed according to the chemical composition, and ball-milled to obtain a powder base material; (2) Two-step molten salt method combined with separation method: In the first step, bismuth oxide, potassium carbonate, niobium oxide and molten salt are synthesized, separated and filtered to obtain a flake precursor. In the second step, the flake precursor is synthesized with potassium carbonate and molten salt, separated and filtered to obtain a sodium niobate flake template. (3) Template grain growth method: the powder base material obtained in step (1) and the sheet template obtained in step (2) are respectively added with a mixed solvent, a dispersant, a plasticizer and a binder to obtain a casting slurry; (4) Casting process: casting the casting slurry obtained in step (3), and then drying to form a thick film; (5) hot pressing process: stacking the thick film obtained in step (4) layer by layer, and finally hot pressing to form a ceramic green body; (6) debinding process: debinding the ceramic green body obtained in step (5) to obtain a ceramic green body; (7) Two-step sintering process: The ceramic body obtained in step (6) is subjected to two-step sintering, cooled to room temperature in the furnace, and then polished with sandpaper of different particle sizes to obtain a ceramic sheet after being polished to a certain thickness; (8) Silver firing process: coating the ceramic sheet obtained in step (7) with silver paste and firing the silver to obtain a ceramic coated with a silver electrode; (9) Polarization process: The ceramic coated with the silver electrode obtained in step (8) is polarized to obtain a potassium sodium niobate-based textured piezoelectric ceramic having high voltage electrical response and temperature stability.

3. The method for preparing a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability according to claim 2, characterized in that: In step (1), ethanol is used as the ball milling medium, and the ball milling time is 12-24 hours.

4. The method for preparing a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability according to claim 2, characterized in that: In step (2), sodium chloride is used as the molten salt, the total mass ratio of the raw material to the molten salt is 1:1.1, the insulation time is 2h, the molar ratio of bismuth oxide, potassium carbonate and niobium oxide in the first step is 6.5:7:10, and the melting temperature is 1050-1100°C, and the molar ratio of the flake precursor to potassium carbonate in the second step is 1:1.75, and the melting temperature is 970-990°C; In step (2), separation is performed using a separation agent, in which sodium tripolyphosphate is used as the separation agent, and the amount of the separation agent added is 8-10wt.% of the total mass of the molten salt mixture corresponding to the first or second step, the stirring speed is 600-800rpm, and the time is 5-10min.

5. The method for preparing a potassium sodium niobate-based textured piezoelectric ceramic having high piezoelectric effect and temperature stability according to claim 2, characterized in that: In step (3), the mixed solvent is butanone and ethanol, the dispersant is triolein, the plasticizer is polyethylene glycol and dibutyl phthalate, the binder is polyvinyl butyral, the mass ratio of the powder base material, the sheet template and the mixed solvent, the dispersant, the plasticizer and the binder is (8.4-9.6): (0.3-0.4): (12-16): (0.3-0.35): (0.75-1.0): (1.1-1.2), the mixing speed is 16-18 r / min, and the time is 6-8h.

6. The method for preparing a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability according to claim 2, characterized in that: In step (4), a casting scraper is used for casting, and the moving speed of the casting scraper is 28-30 cm / min.

7. The method for preparing a temperature-stable potassium sodium niobate-based textured piezoelectric ceramic according to claim 2, characterized in that: In step (6), the debinding temperature is 550-600° C. and the insulation time is 10-12 h.

8. The method for preparing a temperature-stable potassium sodium niobate-based textured piezoelectric ceramic according to claim 2, characterized in that: The two-step sintering in step (7) includes a first step and a second step. The first step has a heating rate of 2-5°C / min, a heating temperature of 1160-1200°C, and no heat preservation. The second step has a cooling rate of 10-15°C / min, a cooling temperature of 1060-1100°C, and a heat preservation time of 8-12h.

9. The method for preparing a temperature-stable potassium sodium niobate-based textured piezoelectric ceramic according to claim 2, characterized in that: In step (8), the diameter of the silver paste is 4-6 mm, the silver sintering temperature is 550-600° C., and the insulation time is 20-30 min.

10. The method for preparing a potassium sodium niobate-based textured piezoelectric ceramic with high piezoelectric response and temperature stability according to claim 2, characterized in that: In step (9), the polarization electric field is 2-4 kV / mm and the time is 20-30 min.

Citation Information

Patent Citations

  • Leaf-free piezoelectric ceramic material with ultra-high-voltage electroresponse and preparation method

    CN107253858A

  • Potassium sodium niobate-based piezoelectric ceramic capable of being sintered in reducing atmosphere and preparation method thereof

    CN109503160A

  • Lead-free texture piezoelectric actuator and preparation method thereof

    CN115968247A

  • Piezoelectric ceramic, its producing method and piezoelectric element using the piezoelectric ceramic

    JP2009242166A

  • Niobate-based lead-free ferroelectric piezoelectric thin film and manufacturing method of the same

    JP2022027517A